2005
DOI: 10.1118/1.1843471
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional IMRT verification with a flat-panel EPID

Abstract: A three-dimensional (3D) intensity-modulated radiotherapy (IMRT) pretreatment verification procedure has been developed based on the measurement of two-dimensional (2D) primary fluence profiles using an amorphous silicon flat-panel electronic portal imaging device (EPID). As described in our previous work, fluence profiles are extracted from EPID images by deconvolution with kernels that represent signal spread in the EPID due to radiation and optical scattering. The deconvolution kernels are derived using Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 21 publications
(21 reference statements)
0
90
0
1
Order By: Relevance
“…The EPID system is calibrated with an X‐rays off measurement and then with a full‐field flood measurement. The full‐field flood is used to normalize the response of all the pixels (similar to the Varian EPID (3) ). This process removes the “horns” from the beam profile.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The EPID system is calibrated with an X‐rays off measurement and then with a full‐field flood measurement. The full‐field flood is used to normalize the response of all the pixels (similar to the Varian EPID (3) ). This process removes the “horns” from the beam profile.…”
Section: Methodsmentioning
confidence: 99%
“…They reported that a glare kernel can be approximated by the sum of two exponentials and that the composite (dose and glare) kernel can be approximated by the convolution of the dose and glare kernels. In another report by Steciw et al (3) the point spread function was represented by a sum of exponentials. This result is used in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations